Implementation of MBKM and the Relationship of Curriculum Policy based on a Case of EFL Education in Japan - Ina Rohiyatussakinah (FKIP, Universitas Banten Jaya, 2021)
The current trend of globalization and development in information technology had boosted the new curriculum of Merdeka Belajar, Kampus Merdeka (MBKM), which has become a universal issue in higher education at several universities in Indonesia. In this demanding and challenging information era in which we live, EFL instruction at higher education institutions needs to offer the students more than general proficiency in English. However, it is not an easy task to design a curriculum at the university level to address these issues. The aim of the research to design a communicative language teaching program developed for teaching English as a foreign language (EFL) at X University. It aims to illustrate the rationale and process of designing a flexible curriculum for university students. This study used a Qualitative research design to present the data. The result clearly showed about The curriculum presented in this paper is intended to be a model for teaching EFL or other foreign languages at higher education institutions based on the case of EFL education in Japan related to MBKM, still relevant to adopt Japan Education policy in our Higher educational program most of them need communicative language teaching for their proficiency in English at higher educational level.